In the beginning was the half-volley: The history of defence in table tennis - revised - Straub, G. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The term "defensive play" is known in many different sports. In the field of racket sports, however, the word defensive player is quite distinct to table tennis. While technically relying to a great extent on backspin defence, defensive players in table tennis are also called "choppers". This article on the technical development of table tennis shows that defensive play in this sport is as old as competitive table tennis itself. Nevertheless, it becomes evident that playing a long-range defence while standing rather far away from the table, as it is commonly known, was originated not earlier than around 1930; this was about three decades after the start of competitive table tennis. It is said that choppers were dominating the early era. Beginning in the 1950s, various alterations in table tennis turned to a decline of backspin defence. Inventions such as rubbers based on sponge and sticky surfaces, the modern topspin stroke (loop drive), the fresh-gluing of rubbers, and the so-called two-color rule favoured offensive play. In this article it is described how defensive players continuously reacted and adapted by finding effective remedies to ensure that defensive play can be a still existing specific style in the world of table tennis.